2006
DOI: 10.1515/bc.2006.069
|View full text |Cite
|
Sign up to set email alerts
|

Tyr-48, a conserved residue in ribotoxins, is involved in the RNA-degrading activity of α-sarcin

Abstract: Residue Tyr-48 in alpha-sarcin is conserved not only within the ribotoxin family, but also within the larger group of extracellular fungal ribonucleases, best represented by RNase T1. A mutant protein in which this Tyr residue was substituted by Phe has been produced and isolated to homogeneity. It was spectroscopically analyzed by means of circular dichroism, fluorescence emission and NMR. Taken together, these results and those from enzyme characterization have revealed the essential role of the -OH group fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…These mutational studies have revealed the involvement of several residues, which are conserved among the different microbial extracellular RNases, in catalysis. Thus, it is well known that His137 and Glu96 are the only residues that are essential for the cleavage reaction performed by α-sarcin [35,45,[70][71][72][73][74][75], whereas His-50, Tyr-48, Arg-121, and Leu-145 mostly contribute to the stabilization of the transition state [45][46][47][48], as stated above. Most of these residues are located in the central β-sheet and their side-chains point towards the concave face of the protein structure where the substrate is supposed to dock [29].…”
Section: Structural Featuresmentioning
confidence: 85%
See 1 more Smart Citation
“…These mutational studies have revealed the involvement of several residues, which are conserved among the different microbial extracellular RNases, in catalysis. Thus, it is well known that His137 and Glu96 are the only residues that are essential for the cleavage reaction performed by α-sarcin [35,45,[70][71][72][73][74][75], whereas His-50, Tyr-48, Arg-121, and Leu-145 mostly contribute to the stabilization of the transition state [45][46][47][48], as stated above. Most of these residues are located in the central β-sheet and their side-chains point towards the concave face of the protein structure where the substrate is supposed to dock [29].…”
Section: Structural Featuresmentioning
confidence: 85%
“…Mutational studies have also revealed that three other active site residues, Tyr48, Arg121, and Leu145, although not essential, appear to be determinants of the ribotoxin activity of α-sarcin [46][47][48]. Studies on the crystal structures of complexes of restrictocin with inhibitors led to the proposal that these ribotoxins may use base flipping to enable cleavage at the correct site of the SRL substrates [49].…”
Section: Ribonucleolytic Activitymentioning
confidence: 99%
“…After more than two decades of systematic studies, it has also become well-established that the activity of ribotoxins is extremely dependent on electrostatic interactions among their active site residues (Álvarez-García et al 2006;Masip et al 2001;Pérez-Cañadillas et al 1998;Pérez-Cañadillas et al 2000). His 42, Glu 66 and His 113 form the catalytic triad of HtA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopic characterization was performed following well-established procedures (Álvarez-García et al 2006;Álvarez-García et al 2009b;García-Ortega et al 2005a;García-Ortega et al 2001;García-Ortega et al 2002;Lacadena et al 1999;Martínez-Ruiz et al 2001). Absorbance measurements were carried out on a Beckman DU640 were also used to calculate their extinction coefficients (Table 1).…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…Cloning procedures, oligonucleotide site-directed mutagenesis, and bacterial manipulations were carried out as previously described [28,38,39]. The mutagenic primers used to substitute the mutated residues are shown in Table 1.…”
Section: Dna Manipulationsmentioning
confidence: 99%